Réponses

  • Utilisateur Brainly
2014-08-27T11:51:32+02:00
Ex 29 :
2(x - 3) - (2x + 1) + 3(5 - 2x)
= 2x - 6 - 2x - 1 + 15 - 6x
= - 6x + 8

Si x = 0 ⇒ - 6*0 + 8 = 8
Si x = - 1 ⇒ - 6*(-1) + 8 = 6 + 8 = 14
Si x = 2/3 ⇒ - 6*2/3 + 8 = - 4 + 8 = 4

Ex 30 :
- 4(1/2x + 1) - x(2 - x) + 7x - x²
= - 2x + 1 - 2x + x² + 7x - x²
= 3x + 1

Si x = 0 ⇒ 3*0 + 1 = 1
Si x = - 1 ⇒ 3*(-1) + 1 = - 3 + 1 = - 2
Si x = 2/3 ⇒ 3*2/3 + 1 = 2 + 1 = 3

Ex 31 :
2x(2 - 3x) - x + 6(x² - x - 2)
= 4x - 6x² - x + 6x² - 6x - 12
= - 3x - 12

Si x = 0 ⇒ - 3*0 - 12 = - 12
Si x = - 1 ⇒ - 3*(-1) - 12 = 3 - 12 = - 9
Si x = 2/3 ⇒ - 3*2/3 - 12 = - 2 - 12 = - 14